ANALISIS KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS SISWA SMP KELAS VII PADA MATERI BENTUK ALJABAR - Sri Wahyu Purwaningsih; Rina Marlina (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2022)
This study aims to observe students' ability to understand the concept of algebraic forms and solve algebraic form problem solving. This research was carried out with the aim of describing the ability to understand students' mathematical concepts in algebraic form material for seventh grade students at SMP Negeri 4 Tambun Utara Bekasi. This research uses descriptive qualitative method. The data collection technique used in this study is a test of the ability to understand mathematical concepts as many as 8 items and documentation. The subjects in this study were seventh grade junior high school students with a total of 20 students as respondents. The data from the research results are based on each category of concept understanding ability, for the high category the percentage is 15%, the medium category is 65%, and the low category is 20%. It was concluded that the students' ability to understand mathematical concepts varied and the majority were in the sufficient category.